EFEKTIFITAS ANTIBAKTERI EKSTRAK BUAH MENGKUDU (Morinda citrifolia, Linn) DALAM MEMBUNUH BAKTERI Enterococcus faecalis - Berti Silviana Intani; Arlina Nurhapsari; Rochman Mujayanto; Rama Putranto (Jurnal Medali, 2013)
Noni fruit (Morinda citrifolia, Linn) consists of antibacterial compound of phenolic. The phenolic derivatives of noni fruit are alizarin, antrakuinon, and acubin, these derivatives can kill bacteria by damaging cell membrane and protein denaturation. The aim of this study is to determine the effectiveness of antibacterial noni fruit extract in killing bacteria Enterococcus faecalis.The study was conducted by making various concentrate of noni fruit extract, that is 100%, 50%, 25%, 12,5%, and 6,25%, and cresophene as the positive control. Testing samples of the bacterium Enterococcus faecalis suspension by putting a disc that has been soaked in various concentrations extract and cresophene on a petri dish, and then incubated for 24 hour, followed with measurement of kiling zone (light zone) around the discs using calipers.The average killing zones formed in extracts 100%, 50%, 25%, 12.5%, 6.25% and cresophene respectively were 13.9 mm, 9.6 mm, 7.3 mm, 6.4 mm , 6mm, and 27.1 mm. The data obtained were tested with One Way Anova and gained a result that there was a difference in the treatment group with significance of 0.000.It can be concluded that noni fruit extract was effective in killing bacteria Enterococcus faecalis.The higher concentration of noni fruit extract, more effective in killing bacteria Enterococcus faecalis.Â Keyword: antibacterial, noni fruit extract, killing zone of Enterococcus faecalis.